Transdermal water-in-oil nanocarriers of nitric oxide for triggering penile erection - Eunryel Nam (Nature Portfolio, 2018)
Abstract Men’s sexual health can have significant effects on a man’s self-esteem, sexual relationship and male reproductive functions. Although commercially available drugs (e.g., VIAGRA and CIALIS) show effective treatment of erectile dysfunction (ED), patients with severe ED fail to respond to these medicines. Topical nitric-oxide (NO) delivery to penis can be a painless, alternative solution with severe ED because NO triggers erection and diffuses to the trabecular arteries and smooth muscles in the penis. We here develop water-in-oil (W/O) nanoemulsions (NEs) that contain NO and can directly spread on the penis. We optimize NE formation conditions including hydrophilic-lipophilic balance (HLB) and ratio of oil, water and surfactants. Then, by spreading NEs on penis skin of intact middle aged dogs, we verify medication effects and safety of the NEs in vivo. The water-in-oil NEs can be a promising non-invasive medication for ED patients with low response to a phosphodiesterase type 5 (PDE5) inhibitor, thus increasing quality of life in the aging society.